EFFECTS OF CPAP USE IN PREVENTING ATRIAL FIBRILLATION RECURRENCE POST-ABLATION IN OSA PATIENTS - Sumeet S. Mutti, MD (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD Risk Factors Background: With the escalating global prevalence of atrial fibrillation (AF) and its recognized link to obstructive sleep apnea (OSA), this study focuses on assessing the efficacy of continuous positive airway pressure (CPAP) therapy in reducing AF recurrence following catheter-based pulmonary vein isolation. Methods: Following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines, we conducted a comprehensive systematic review and meta-analysis. The search was limited to English-language journal articles published from 2010 up to June 2023. Our search spanned various databases, targeting studies reporting AF recurrence post-ablation exclusively in patients diagnosed with OSA with AHI > five. After stringent selection criteria, we applied the Mantel-Haenszel method for analysis, using the pooled relative risk (RR) as the core outcome measure. Results: Data from Five studies with 1023 in total patients from three cohort studies and two intention-to-treat Randomized Control Trial was extracted. Both common effect and random effects models consistently demonstrated a substantial reduction in AF recurrence post-ablation attributed to CPAP intervention, yielding pooled RRs of 0.6075 and 0.6101, respectively. Patients who used CPAP showed 39.1% relative risk reduction (in the random effect model) of AF recurrence post-ablation compared to those who did not use CPAP. Heterogeneity analysis indicated moderate variability, and Egger's test suggested minimal risk of publication bias. Conclusions: The findings highlight the potential of CPAP therapy in significantly curtailing AF recurrence among individuals with OSA, particularly in the context of post-ablation scenarios. CPAP's influence may extend to rectifying atrial structural and electrical remodeling, translating into a tangible decrease in AF recurrence rates.